2009
DOI: 10.1007/s11998-009-9231-z
|View full text |Cite
|
Sign up to set email alerts
|

Electroless nickel–phosphorus deposition on carbon steel CK-75 and study of the effects of some parameters on properties of the deposits

Abstract: Electroless nickel-phosphorus (Ni-P) deposition provides coatings with high hardness and excellent resistance to wear and abrasion. In this study, autocatalytic deposition of Ni-P alloy has been carried out on steel CK-75 sheets from bath containing nickel sulfate hexahydrate, sodium hypophosphite hydrate, thiourea, lactic acid, and sodium acetate. The effects of lactic acid concentration, pH and temperature on deposition rate, composition of deposits, and hardness have been studied. Also the changes in the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…hardness, crystallinity, and CTE [12,13]. For tailoring these properties, the phosphorous content can be manipulated via the deposition parameters of the used electrolyte [14]. NiP with a phosphorous content higher than 10.5 wt% is referred to as X-ray amorphous [15].…”
Section: Electroless Nipmentioning
confidence: 99%
“…hardness, crystallinity, and CTE [12,13]. For tailoring these properties, the phosphorous content can be manipulated via the deposition parameters of the used electrolyte [14]. NiP with a phosphorous content higher than 10.5 wt% is referred to as X-ray amorphous [15].…”
Section: Electroless Nipmentioning
confidence: 99%
“…In this crystallization process, the a-Ni-P is heated to the annealing temperature (600 • C) in the nitrogen gas atmosphere, and the temperature is maintained for 1 h to make sure that the crystallization process progresses completely. According to the reported literature the as-deposited amorphous Ni-P changes to crystalline Ni and crystalline Ni 3 P under this heat treatment process [22,23].…”
Section: Ni-p Crystallizationmentioning
confidence: 89%
“…[8][9][10][11][12] Some investigations have also been done concerning the influences of the concentrations of metal salt, reducing agents, complexing agents, temperature, pH, and additives on the deposition rate. [13][14][15] Plating rate is of importance in EN plating, with both too fast or too slow being undesirable. 16 On the one hand, a loosely adherent layer will be formed on the substrate if gases generated at a high rate cannot diffuse away from the reaction interface instantly.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] A number of researchers have all concluded that the rate of deposition increases with an increase in hypophosphite concentration, pH, or temperature, but decreases with increasing complexing agents' concentration. 11,14,21,23 However, most researchers had just described the dependence of rate on various parameters, and not focused on the dynamic equations. 11,14,25,26 Based on a previously proposed mechanism, Malecki et al derived an empirical deposition rate equation in an acid EN plating bath, which agreed well with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation